Penguatan Warisan Budaya Caturhajo melalui Transformasi Penulisan Naskah Ketoprak - Desta Rizky Kusuma; Yosi Wulandari; Sadr Lufti Mufreni; Nur Isna Oktaviani Alkholili; Nuurul Mukhlisah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to strengthen local cultural heritage through the transformation of ketoprak scriptwriting in Caturharjo Village, Pandak Sub-district, Bantul Regency. The program was implemented as part of the 2025 Community Empowerment by Students (PMM) initiative of Ahmad Dahlan University using a qualitative method and field study approach. Preliminary observations revealed low literacy in ketoprak script development, limited innovation in performances, and insufficient utilization of digital technology for documentation and promotion of traditional arts. Based on these findings, a series of training activities were conducted, including ketoprak scriptwriting, performance capacity building, script digitalization, social media management, and audiovisual documentation workshops. The results indicate significant improvement in community capacity, evidenced by the successful development of a ketoprak script based on local historical narratives and increased understanding of digitalization and promotion by 34.8% and 34.1%, respectively. This program has positively influenced community participation in cultural preservation, provided digitally archived scripts, and enhanced cultural promotion strategies through technology. These efforts open opportunities for strengthening local cultural ecosystems and developing community-based creative economies in Caturharjo.